1992
DOI: 10.1029/92wr01170
|View full text |Cite
|
Sign up to set email alerts
|

Well catchments and time‐of‐travel zones in aquifers with recharge

Abstract: The classical analytical method used to map catchments and time‐of‐travel zones of pumping wells was originally derived for another purpose and takes no account of recharge (Bear and Jacobs, 1965). Generalized catchment shapes are presented here for aquifers with recharge. They can be scaled to field situations through two or three nondimensional parameters. A semianalytical path line tracing model was used to generate the shapes. It contains new expressions for pore water velocities in two infinite strip, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 8 publications
3
22
0
1
Order By: Relevance
“…Groundwater models play an important role in decision-making processes (Reichert and Pahl, 1999), especially in the context of better characterization of parameter distributions and prediction of dynamic behavior of a given system. Groundwater models are helpful tools to define well capture zones based on hydrogeological and water supply operation data (e. g., Kinzelbach et al, 1992;Lerner, 1992). They allow one to study the sensitivity of the observed system with respect to changing parameters and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater models play an important role in decision-making processes (Reichert and Pahl, 1999), especially in the context of better characterization of parameter distributions and prediction of dynamic behavior of a given system. Groundwater models are helpful tools to define well capture zones based on hydrogeological and water supply operation data (e. g., Kinzelbach et al, 1992;Lerner, 1992). They allow one to study the sensitivity of the observed system with respect to changing parameters and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bhatt [1993] investigated the influence of the main aquifer properties on the transverse and longitudinal extent of a capture zone in a confined aquifer. The influence of recharge was investigated by Lerner [1992], who derived analytical equations for the isochrones in two different, recharged aquifer systems. Kinzelbach et al [1992] studied well catchments in a recharged aquifer in both two and three spatial dimensions.…”
Section: -1297/98/98 Wr-0155250900mentioning
confidence: 99%
“…Bear and Jacobs [1965] derived the general equation of isochrones for flow toward a fully penetrating, steady state well in an infinite, homogeneous, and isotropic confined aquifer. Lerner [1992] extended this to investigate the influence of a spatially homogeneous recharge on well catchments in two dimensions. Kinzelbach et al [1992] determined isochrone shapes in both two and three dimensions in a quasi-homogeneously recharged aquifer and provided a dimensionless number to determine whether a two-dimensional approximation of the flow field is appropriate or not.…”
Section: Introductionmentioning
confidence: 99%